A scoping review of the impact of eco-distress and coping with distress on the mental health experiences of climate scientists - Calabria, Luis; Marks, Elizabeth (Frontiers in Psychology, 2024)
Introduction In the face of a future predicted to be one defined by an increase in the Earth’s surface temperature, and the associated extreme weather events, distressing emotional responses are understandable. Climate scientists comprise a unique group, in that they are deeply and consistently faced with the current reality, and consequences of, climate change. ‘Ecological distress’, a term to describe climate-related emotional experiences, can include feelings of grief, anxiety, and hopelessness proportionate to the existential threat of climate change. Methods This review sought to scope the current literature into how ecological distress is experienced by this population, factors that mitigate or exacerbate these experiences, and the coping strategies that are used. This review used Interpretive Content Analysis to code the data and employed a narrative synthesis of the findings. Results This paper demonstrates the significant emotional impacts associated with working as a climate scientist, along with an associated set of coping strategies. Climate scientists share experiences of emotional distress, involving both intra- and interpersonal processes, highlighting how people working in this profession may be vulnerable to unique pressures and psychological burdens related to their work. Discussion Climate scientists have an essential role to play in helping society and policy makers understand the implications of climate change and identifying the most useful responses. As such, it is integral that the psychological wellbeing of this group is understood and cared for. This review is the first step in synthesising current knowledge, in preparation for developing helpful methods and strategies for keeping our climate scientists well, motivated, and engaged.